(3EQTGO GdWdGH Edi Yde GdMSGHs
(3ChdgG (B:s
(3CeG HYO MeO Gddg eaJJM GdcJGH heNJJe OYhi Cgd GdKhGH ai OGQ GdeBH aYde GdMSGH ef GdYdhe GdLdjdI dGeMGdI s
(3BNQgG (B:s
(3gPG BNQ eG CQOJg s
(3GdeDda ef YdeGA ChGNQ GdbQf GdKGef hChGFd GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B7 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3144) s
Keywords: (3GdQjGVjGJs